2020
DOI: 10.3389/fphar.2020.551911
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Bioavailability of Boswellic Acid by Piper longum: A Computational and Pharmacokinetic Study

Abstract: Chronic inflammation is a key culprit factor in the onset and progression of several diseases. Novel and pharmacologically effective therapeutic approaches are needed for new treatment remedy or improved pharmacokinetics and pharmacodynamics for existing synthetic drugs, in particular natural products. Boswellic acids are well-known natural products, with capacity to effectively retard inflammation without severe adverse effects. However, the therapeutic use of Boswellic acids are greatly hindered by its poor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…Piper longum extract was found to increase the bioavailability of boswellic acid ( p < .05). The results confirmed that P. longum may be administered orally with boswellic acid together for effective therapeutic efficacy (Vijayarani et al, 2020). Oxytetracycline (OTC) is used for the treatment of various bacterial, rickettsial, and mycoplasmal infections of poultry and other avian species.…”
Section: Piper Longum As Bioavailability Enhancersupporting
confidence: 74%
“…Piper longum extract was found to increase the bioavailability of boswellic acid ( p < .05). The results confirmed that P. longum may be administered orally with boswellic acid together for effective therapeutic efficacy (Vijayarani et al, 2020). Oxytetracycline (OTC) is used for the treatment of various bacterial, rickettsial, and mycoplasmal infections of poultry and other avian species.…”
Section: Piper Longum As Bioavailability Enhancersupporting
confidence: 74%
“…In addition, the bioavailability of the active ingredients after conventional use of chewable B. serrata has not yet been published. To overcome the poor bioavailability of the concentrated or isolated boswellic acids, attempts have been made to enhance the bioavailability by the combination of Piper longum (long pepper) and by producing specific compounds such as boswellic acids attached to phospholipids or incorporated into micelles (Hüsch et al 2013 ; Meins et al 2018 ; Vijayarani et al 2020 ). On the basis of the aforementioned studies, it is clear that B. serrata extract and boswellic acids may have a therapeutic effect against virus-induced secondary microbial infection and may be effective in preventing COVID-19 causing secondary infection and COVID-19 causing complications.…”
Section: Potential Therapeutic Effects Of Boswellic Acids and B Serrata Extract Against Covid-19-induced Secondary Micmentioning
confidence: 99%
“…To investigate the absorption, distribution, metabolism, and elimination (ADME) properties of alloxan and phenytoin, we used Schrödinger release 2021–1: (QikProp, Schrödinger, LLC, New York, NY, USA). QikProp was used to estimate various pharmacokinetic and pharmacodynamic properties (solvent accessible surface area [SASA], a hydrophobic component of SASA [FOSA], a hydrophilic component of SASA [FISA], carbon and attached hydrogen) component of the SASA [PISA–π], number of metabolites [#], CNS distribution, predicted brain/blood partition coefficient [QPlog BB], estimated number of donor hydrogen bonds [Donor HB], estimated number of accepted hydrogen bonds [Accept HB], logP, and % human oral absorption [percentage]) [5] .…”
Section: Methodsmentioning
confidence: 99%